2015
DOI: 10.12659/msm.892160
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Bone Morphogenetic Protein-2 Levels in Serum and Synovial Fluid with Disease Severity of Knee Osteoarthritis

Abstract: BackgroundThis study aimed to investigate the bone morphogenetic protein-2 (BMP-2) levels in serum and synovial fluid (SF) of patients with primary knee osteoarthritis (OA) and to exam its correlation with radiographic and symptomatic severity of the disease.Material/MethodsA total of 37 knee OA patients and 20 healthy controls were enrolled in this study. Knee OA radiographic grading was performed according to the Kellgren-Lawrence (KL) grading system by evaluating X-ray changes observed in anteroposterior kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 42 publications
(48 reference statements)
2
16
2
1
Order By: Relevance
“…BMP deregulation has already been observed in SpA patients’ serum; however, to our knowledge, this is the first study assessing BMP levels in SpA patients’ SF. The consistency of our results was validated with respect to previous studies that assessed BMP contents in SF from OA patients [ 31 34 ]. Three independent studies have demonstrated that BMP-2 serum concentration was in the range of 100 pg/mL and neatly higher in ankylosing spondylitis patients than in healthy controls [ 14 , 15 , 35 ].…”
Section: Discussionsupporting
confidence: 86%
“…BMP deregulation has already been observed in SpA patients’ serum; however, to our knowledge, this is the first study assessing BMP levels in SpA patients’ SF. The consistency of our results was validated with respect to previous studies that assessed BMP contents in SF from OA patients [ 31 34 ]. Three independent studies have demonstrated that BMP-2 serum concentration was in the range of 100 pg/mL and neatly higher in ankylosing spondylitis patients than in healthy controls [ 14 , 15 , 35 ].…”
Section: Discussionsupporting
confidence: 86%
“…BMP-2 expression was significantly greater in OA cartilage than in normal cartilage. Patients with severe X-ray knee OA showed significantly increased BMP-2 levels in the serum and synovial fluid compared with those with moderate OA [ 35 ]. BMP-2 concentrations in the serum and synovial fluid of knee OA patients were closely related to the radiographic and symptomatic severity of knee OA [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe X-ray knee OA showed significantly increased BMP-2 levels in the serum and synovial fluid compared with those with moderate OA [ 35 ]. BMP-2 concentrations in the serum and synovial fluid of knee OA patients were closely related to the radiographic and symptomatic severity of knee OA [ 35 ]. Moreover, an increase in BMP-2 levels in mice resulted in severe aggravation of osteophyte formation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individual variation in endogenous levels of such factors could contribute to differences in both in vitro properties of MSC as well as in vivo properties of MSCs affecting the healing responses upon THA surgery, although clinical evidences are limited. Increased serum levels of BMP-2 have been found in patients with knee OA compared to healthy controls ( Liu et al, 2015 ). Such variations in BMP-2 levels cannot be ruled out as an underlying contributing factor to the observed differences in OB-capacity and osseointegration in the current study.…”
Section: Discussionmentioning
confidence: 99%